PEMETAAN DAERAH ALIRAN SUNGAI LELEMA DAN KONDISI FISIK JARINGAN IRIGASI DI DESA POPONTOLEN BERBASIS SISTEM INFORMASI GEOGRAFIS - Kristianto Pisu; Daniel P.M Ludong; David p. Rumambi (COCOS, 2018)
ABSTRACT The watersheds is an ecosystem and the main elements of this ecosystem are natural resources (land, water and vegetation) and human resources that utilize natural resources. Regarding with the relationship between watershed and irrigation as one component in the water resources management, watersheds determine the availability of irrigation water when the watershed ecosystem is disrupted. In this condition, the water supply for irrigation decreased and therefore the agricultural productivity reduced. The area of the Lelema Watershed is 3,095 ha with a main river as long as 12,787 m that ends in the main river of Nimanga. The irrigated area of the Popontolen village is geographically located in the irrigation area of Popontolen Village that is located at 1o15'47 "- 1o16'40" LU and 124o36'20 "- 124o38'00" BT. The area of Popontolen irrigation is 121.20 ha and consisted of primary, secondary and tertiary channels. In conclusion, the carrying channel in the irrigation area of the Popontolen Village is 7,468 meters and the length of primary and secondary carrier channels are 213 and 3,131 m, respectively. Keywords: Lelema Watershed, Technical Irrigation, Geographic Information System.